DEVELOPMENT OF CLOSED LOOP CONTROL OF CASCADED H-BRIDGE MULTILEVEL INVERTER FOR PHOTOVOLTAIC APPLICATION - Hamidun, Mohd Arif Ikhwan (2017)
In this project cascaded H-bridge multilevel inverter topology is presented with sine pulse width modulation technique as a triggering pulse for the inverter. Due to the capabilities of multilevel inverter by using low voltage dc source as an input and produce the alternating voltage that been desired as an output. Closed loop control also implemented in this project to increase the efficiency percentage of the total harmonic distortion. This paper involve with 3-level and 5-level cascaded H-bridge multilevel inverter with respect of the total harmonic distortion, number of switches and output voltage by performing simulation using Simulink and implemented it to the hardware form. To demonstrate the effectiveness of this topologies, an experimental system was executed.